The determinants of retail pharmacists’ retention with a mediating effect of continuance commitment / Nurul Izzati Azmi - Azmi, Nurul Izzati (2020)
Retail pharmacy is a business which supplies a prescription or non-prescription medicines when legally permitted to the community. The main objective of the retail pharmacy is to provide quality pharmacy services to improve the community’s health. However, their objective cannot be achieved if there is an increase in turnover rates among retail pharmacists in Malaysia. According to the interview conducted with one of the biggest retail pharmacies in Malaysia, in 2018, 20% of their pharmacists resigned and they were reluctant to stay even when they were offered a higher salary compared to other competitors. Therefore, to overcome the issue of turnover rates among retail pharmacist, this study was designed to examines the determinants of retail pharmacists’ retention with a mediating factor. The independent variables for this study are transformational leadership, job satisfaction, and procedural justice. Meanwhile, employee retention is the dependent variable. This study also investigated a mediating effect of continuance commitment towards the relationship between independent and dependent variables. The selected sample for this study is the retail pharmacists in Negeri Sembilan and Pahang which involved 155 samples. The questionnaire was used to collect the primary data. The collected data were analyzed using SPSS software. This study revealed that all independent variables have a positive and direct effect on employee retention. The findings also found that continuance commitment is not a suitable mediator for the selected variables and sample due to respondents’ demographic characteristics. This study is expected to bring new knowledge in the employee retention studies and can be a valuable reference for a retail pharmacy to develop strategies to sustain their valuable pharmacist.